الرؤيا الشعرية ومرجعياتها عند أدونيس - كلفالي, سميحة (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
اعتمد الكثير من منظري النقد الأدبي الحداثي على التجربة الغربية في تأسيس مفاهيم جديدة للأدب عامة وللشعر خاصة ، وفي هذا المقال سأقف عند مفهوم الرؤيا الشعرية ومرجعياتها عند أدونيس ، فقد اتفق جل الرواد على قيامه عليها بالدرجة الأولى، ويعد أدونيس من أبرزهم ، ذلك أنه قد أعلن تجاوزه للقواعد الكلاسيكية التي قامت عليها الشعرية العربية مستثمرا مبادئ نظيرتها الغربية. Abstract : Many contemporary Arab Criticists have relied on the Western experience in establishing new concepts about literature generally and poetry particularly . In this article I will shed the light on the concept of poetic vision and its references to Adonis . MOSTof the poineers agreed that he was the first one interested with it , Adonis is considered as the most prominent of them , were he declared that he exceeded the classical rules on which the Arab poetry was based on investing its Western counterpart’s principles .